Digitalisasi Birokrasi Terkait Mekanisme Pengawasan Pekerja Migran Indonesia Dalam Konteks Peran Negara Sebagai Protektor Bagi Warga Negaranya - Jati, I Putu Gede Suastika; Herawati, Kadek Mery; Dwiyanti, Ida I Dewa (Indra Institute Research & Publication, 2023)
The placement program for Indonesian workers abroad is one way to overcome the problem of unemployment. The government's role in this aspect is focused on the aspect of coaching, as well as protection and providing various facilities to related parties, especially Indonesian Migrant Workers and placement service companies concerned. How is the Digitalization of the Bureaucracy related to PMI Oversight mechanisms in the context of the State's role as a Protector for its citizens. This type of research is normative juridical law, namely research that refers to legal norms contained in laws and regulations and court decisions as well as norms that live and develop in society. The E-KTKLN itself is mandatory for all prospective Indonesian Migrant Workers and Indonesian Migrant Workers who are placed abroad, the personal data of the Prospective Indonesian Migrant Workers is inputted into a system called SISTOKTKLN or Computerized Overseas Worker Card System. To protect Indonesian migrant workers, the Indonesian government offers two types of protection to foreign migrant workers. First, preventive/educational protection, which can be pursued, among other things, through the creation of legal instruments, including protecting migrant workers, such as laws and implementing regulations governing migrant workers, bilateral or multilateral agreements governing the mechanism for the placement of migrant workers and their protection for the wearer.